Therapeutic writing through the lens of the grief memoir and dialogical self theory. Issue 2 (3rd April 2021) - Den Elzen, Katrin
Abstract: This article contributes to the theorizing and clinical use of therapeutic writing in psychotherapy through the lens of the grief memoir. To this end it undertakes an analysis of two memoirs, Lucie Brownlee's Life After You (2014) and Susan Duncan's Salvation Creek (2006). This research draws and expands on James Pennebaker's expressive writing paradigm and links autobiographical writing to Dialogical Self Theory. It identifies how the authors voice subject positions such as the bereaved self and the remembered other, and, importantly, how writing positions and repositions such selves to facilitate the rebuilding of identity disrupted by loss and recovery from grief.